The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/s1368980022001124
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel exploration of individual- and community-level factors contributing to overweight and obesity among reproductive-aged women: a pooled analysis of Bangladesh Demographic and Health Survey, 2004–2018

Abstract: Objectives: Overweight and obesity have been related to a variety of adverse health outcomes. Understanding the overweight and obesity epidemic in Bangladesh, particularly among reproductive-aged women, is critical for monitoring and designing effective control measures. The purpose of this study was to determine the prevalence of overweight and obesity in reproductive-aged women and to identify the risk factors of overweight and obesity. Design: A total of 70,651 women were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These ndings corroborate the ndings of previous studies among women of reproductive age in Nigeria. [11,16,21,22,25,26] In the present study, the associations were such that women who were older, more educated, Christians, with more children, from richer households and who had more educated spouses had higher odds of being obese. This pattern of relationship has also been previously reported by studies among women of reproductive of age within and outside Nigeria.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…These ndings corroborate the ndings of previous studies among women of reproductive age in Nigeria. [11,16,21,22,25,26] In the present study, the associations were such that women who were older, more educated, Christians, with more children, from richer households and who had more educated spouses had higher odds of being obese. This pattern of relationship has also been previously reported by studies among women of reproductive of age within and outside Nigeria.…”
Section: Discussionmentioning
confidence: 56%
“…This study showed that sub-national variations exist in the prevalence of obesity among non-pregnant women of reproductive age in the different states of Nigeria, even after adjusting for a wide range of commonly reported individual, household and community level predictors. Such variations have been observed in studies carried out in the United States, [15] Bangladesh, [21,22] Cambodia, [23] China, [24] and particularly in Africa. [11,14,[25][26][27] The nding of this study is important because it highlights the role of the contextual unit or the environment in which a woman lives in the prevalence of obesity.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Notably, reports indicate a consistent rise in the prevalence of overweight and obesity in this age group, increasing from 3% in 2000 to 8% in 2016 in Ethiopia ( 44 ). The prevalence of overweight and obesity reached an alarming level in some developing countries such as 50.4% in Tanzania ( 45 ), 35.2% in Bangladesh ( 46 ), and 55.20% in Brazil ( 47 ). This shows the urgent need for targeted interventions and policies to address this growing issue and improve the health outcomes of women and their children.…”
Section: Discussionmentioning
confidence: 99%